Local-scale spatial structure and community composition of orchid mycorrhizal fungi in semi-natural grasslands - Oja, Jane; Vahtra, Johanna; Bahram, Mohammad; Kohout, Petr; Kull, Tiiu; Rannap, Riinu; Kõljalg, Urmas; Tedersoo, Leho (Mycorrhiza, 2017)
Orchid mycorrhizal (OrM) fungi play a crucial role in the ontogeny of orchids, yet little is known about how the structure of OrM fungal communities varies with space and environmental factors. Previous studies suggest that within orchid patches, the distance to adult orchids may affect the abundance of OrM fungi. Many orchid species grow in species-rich temperate semi-natural grasslands, the persistence of which depends on moderate physical disturbances, such as grazing and mowing. The aim of this study was to test whether the diversity, structure and composition of OrM fungal community are influenced by the orchid patches and management intensity in semi-natural grasslands. We detected putative OrM fungi from 0 to 32 m away from the patches of host orchid species (Orchis militaris and Platanthera chlorantha) in 21 semi-natural calcareous grasslands using pyrosequencing. In addition, we assessed different ecological conditions in semi-natural grasslands but primarily focused on the effect of grazing intensity on OrM fungal communities in soil. We found that investigated orchid species were mostly associated with Ceratobasidiaceae and Tulasnellaceae and, to a lesser extent, with Sebacinales. Of all the examined factors, the intensity of grazing explained the largest proportion of variation in OrM fungal as well as total fungal community composition in soil. Spatial analyses showed limited evidence for spatial clustering of OrM fungi and their dependence on host orchids. Our results indicate that habitat management can shape OrM fungal communities, and the spatial distribution of these fungi appears to be weakly structured outside the orchid patches.
Keywords: Fungal community composition; Soil Microbiology; Mycorrhizae; Grassland; Calcareous grassland; mykorhiza; pastviny; Orchidaceae; Basidiomycota; Estonsko; půdní mikrobiologie; Spatial distribution; Phylogeny; fylogeneze; Grazing intensity; Orchid mycorrhiza; Next-generation sequencing; Estonia